Colonized patients by Candida auris: Third and largest outbreak in Brazil and impact of biofilm formation - de Melo, Camylla Carvalho; de Sousa, Bruna Rodrigues; da Costa, Gisela Lara; Oliveira, Manoel Marques Evangelista; de Lima-Neto, Reginaldo Gonçalves (Frontiers in Cellular and Infection Microbiology, 2023)
Objective: To describe the clinical-epidemiological features of patients colonized by Candida auris in the largest outbreak in Brazil, and to show the biofilm formation capacity of yeast strains. Methods: Clinical yeasts suspected of Candida auris isolated from urine and surveillance samples were seeded on chromogenic media at 30°C, and Sabouraud agar at 42 °C. MALDI-TOF MS was used for reliable identification. After proteomic confirmation, genomic approach and culture on Chromagar Candida Plus media were carried out. Biofilm formation was investigated based on metabolic activity, and clinical-epidemiological profile of patients were described. Results: Eleven Candida auris from nine patients were identified between end of December, 2021, and March, 2022. Two clinical yeast were isolates from urine and nine axillary and inguinal surveillance swab. None case is related to previuos SARS-CoV-2 infection. However, all the yeasts showed high ability biofilm formation. Conclusion: C. auris requires great vigilance, as its high capacity to colonize and form biofilms contributes to its dissemination. The rapid and precise identification of this species is essential for the management, control, and prevention of infections.